On the Approximability of TSP on Local Modifications of Optimally Solved Instances - Böckenhauer, Hans-Joachim; Forlizzi, Luca; Hromkovič, Juraj; Kneis, Joachim; Kupke, Joachim; Proietti, Guido; Widmayer, Peter (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2007)
Given an instance of TSP together with an optimal solution, we consider the scenario in which this instance is modified locally, where a local modification consists in the alteration of the weight of a single edge. More generally, for a problem U, let LM-U (local-modification-U) denote the same problem as U, but in LM-U, we are also given an optimal solution to an instance from which the input instance can be derived by a local modification. The question is how to exploit this additional knowledge, i.e., how to devise better algorithms for LM-U than for U. Note that this need not be possible in all cases: The general problem of LM-TSP is as hard as TSP itself, i.e., unless P = NP , there is no polynomial-time p(n)-approximation algorithm for LM-TSP for any polynomial p. Moreover, LM-TSP where inputs must satisfy the -triangle inequality (LM- -TSP ) remains NP-hard for all > 12 . However, for LM- -TSP (i.e., metric LM-TSP), we will present an efficient 1.4-approximation algorithm. In other words, the additional information enables us to do better than if we simply used Christofides’ algorithm for the modified input. Similarly, for all 1 < < 3.34899, we achieve a better approximation ratio for LM- -TSP than for -TSP. For 12 ≤ < 1, we show how to obtain an approximation ratio arbitrarily close to 1, for sufficiently large input graphs.